Mutiny : the rise and revolt of the college-educated working class - Scheiber, Noam (Farrar, Straus and Giroux, 2026)
"The story of a disillusioned generation that set out to reclaim its dignity and take on corporate America. In recent years, young college grads have faced an alarming reality: crushing debt, unemployment, and jobs below their qualifications. They are frustrated that the time and money they invested in a degree have failed to bring about the opportunities they were promised. The anger of this college-educated working class began to boil over during the Covid pandemic, when workers at companies like Apple and Starbucks shocked corporate America by voting to unionize. Not long after, the veteran New York Times reporter Noam Scheiber met Chaya Barrett, an astute college grad and eight-year Apple employee who had helped organize her coworkers at an Apple store near Baltimore. While following Barrett and her cohort as their seemingly spontaneous rebellions spread far and wide--from college-educated workers at Apple stores and Starbucks cafés, through video-game studios, and even to Hollywood writers' rooms--Scheiber realized he was witnessing something deep and lasting. Mutiny is the revelatory account of a generation made confident by their historic educational achievements, only to become disillusioned when their degrees yielded far less than they were taught to expect. With striking empathy, Scheiber paints a vivid portrait of this new working class while telling the dramatic story of its revolt against the status quo. He describes how recent developments like the proliferation of artificial intelligence and the war in Gaza have further fueled its discontent, and he explains why the college-educated working class will continue to demand change in the workplace, in cities like New York, and in national politics for years to come."-- Provided by publisher.